Evropske digitalne denarnice EUDIW in EBW: od regulative do prakse - Domajnko, Martin; Keršič, Vid; Turkanović, Muhamed (OTS 2026 Sodobne informacijske tehnologije in storitve: Zbornik 29. konference, 2026)
In this paper, we present the European digital identity framework, focusing on the European Digital Identity Wallet (EUDI) for individuals and the proposed European Business Wallet (EBW) for legal entities. We focus on the regulatory framework, participant roles and the trust model underlying the wallets, as well as on the technical architecture, including digital credentials, the SD-JWT VC and mdoc formats, and the OpenID4VCI and OpenID4VP protocols. We demonstrate the practical use of digital wallets with a reference implementation of a digital credential issuer and verifier, and an example of logging into a web service with an EUDI wallet. In the discussion, we compare the maturity levels of both frameworks and discuss the opportunities and requirements for organizations to integrate into the emerging European digital wallet ecosystem.